Reconsidering the Nehushtan as a Magical Healing Device within the Geographical, Cultural, and Magico-Religious Context of the Ancient Near East - Williams, Gillian (Religions, 2023)
According to Numbers 21:4–9, the Nehushtan was a copper/bronze snake effigy that functioned as a ‘magical’ healing tool to cure the early Israelites from venomous snakebites they incurred during their desert wanderings. What is unclear from the narrative is the symbolic significance of the event, the materials used, the technical skills required, and whether magic was at play. Firstly, when considering the magical effects of the Nehushtan, we must define which type of magic—apotropaic or sympathetic—was involved. Based upon existing scholarship on the topic, the general consensus is that the Nehushtan represented sympathetic magic, underpinned in this instance by homeopathic/imitative magic. To highlight this point, this study will provide selected examples of both types of magic so that the Nehushtan’s association with sympathetic magic can be illustrated. Secondly, and most importantly, we must consider why the image of a snake was chosen if the very affliction (envenomation) suffered by the people was caused by the creature now being posited as a symbol of divine healing. Did the ancient perceptions of snakes and healing play a role in this decision? Why did the early Israelites not question the logic behind the use of a magical snake effigy when both magic and effigies were technically prohibited by biblical laws? To answer these questions, the study will consider the historical background (the Exodus from Egypt), the set (geographical location), and the setting (cultural contact and influence) in which the narrative of the Nehushtan took place.